PENGARUH PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP KINERJA PEGAWAI SATUAN POLISI PAMONG PRAJA KOTA PROBOLINGGO - Saiful Bahri; Bachtiar Irawan; Tumini Tumini (Universitas Bina Taruna Gorontalo, 2022)
The research was conducted at the Satpol PP Probolinggo city with the aim of knowing how the impact of career development and compensation on performance. This study is a causal associative type, with a purposive sampling approach. Samples were taken as many as 57 employees from a population of 172 Satpol PP employees of Probolinggo city. The results of this study indicate that the Fcount 59.827 >Ftable 3.17 and a significance value of 0.000 <0.05, meaning that career development and compensation together affect performance. Likewise, partially, career development and compensation have a value of thit>ttab with a value of sig < 0.05, meaning that separately career development and compensation have an influence on performance. The contribution of career development and compensation to performance is 68.9%, and 31.1% the influence of other variables outside the study. While the biggest influence on performance is career development with a beta coefficient of 0.700.